Enhancing soil carbon stocks and soybean yields in coastal areas through the application of biofertilizers - Bertham, Yudhi Harini; Utami, Kartika; Putri, Elsa Lolita; Arifin, Zainal; Kamarudin, Khairun Nisa (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Climate change driven by increased concentration of greenhouse gases in the atmosphere has a significant impact on agricultural systems, particularly in coastal areas that are prone to rising salinity and decreased soil quality. The application of biofertilizers as a strategy for enhancing soil carbon stocks is crucial, given their role in promoting microbial activity and nutrient availability, leading to soil fertility. This study aimed to evaluate the role of biofertilizers in increasing soil carbon stocks and soybean yields in coastal areas. The research was conducted from April to December 2024 in Bengkulu City. The field experiment was designed in a split-plot design, with the main plot was soybean varieties at two levels (i.e., Anjasmoro and Dering I), and the subplot was fertilizer inputs at four levels (i.e., recommended inorganic fertilizer, AMF + Bradyrhizobium + potassium solvent, Bradyrhizobium + phosphate solvent + potassium solvent, and Bioenzyme). The application of biofertilizers and bioenzymes effectively increased soil carbon stock. The potassium-solubilizing microbial population had a greater influence on carbon stocks than the phosphate-solubilizing population and AMF. The use of biofertilizers and bioenzymes also improved soil biological properties and nutrient absorption, thereby contributing to increase soybean yields. This study provides evidence to support government policies promoting biofertilizer use in agriculture, including training and extension programs for farmers, particularly in coastal areas, to improve soil quality, enhance yields, and reduce dependence on chemical fertilizers which are often expensive and can degrade soil quality in the long term.